1996
DOI: 10.1016/s1074-5521(96)90082-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of inhibitors of bacterial d-alanine: d-alanine ligases

Abstract: VanA has greatly reduced affinity for all the ligands studied. The relative affinities of the inhibitors in the reversible binding step are not, however, consistent with the substrate specificities of the enzymes. We propose a mechanism in which proton transfer from the attacking nucleophile to the departing phosphate occurs directly, without intervention of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
66
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 23 publications
1
66
0
1
Order By: Relevance
“…The tight binding of D-cycloserine to DDl suggests that the antibiotic binds to the high-affinity D-alanine site (10). Compounds designed to mimic the Dalanine:D-alanine dipeptide or the reaction transition-state intermediates led to the developments of phosphinate and phosphonate dipeptide analogs (11)(12). These phosphinates or phosphonates, after being phosphorylated by DDl, bind to the protein tightly and inhibit the reaction (11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tight binding of D-cycloserine to DDl suggests that the antibiotic binds to the high-affinity D-alanine site (10). Compounds designed to mimic the Dalanine:D-alanine dipeptide or the reaction transition-state intermediates led to the developments of phosphinate and phosphonate dipeptide analogs (11)(12). These phosphinates or phosphonates, after being phosphorylated by DDl, bind to the protein tightly and inhibit the reaction (11)(12).…”
mentioning
confidence: 99%
“…Compounds designed to mimic the Dalanine:D-alanine dipeptide or the reaction transition-state intermediates led to the developments of phosphinate and phosphonate dipeptide analogs (11)(12). These phosphinates or phosphonates, after being phosphorylated by DDl, bind to the protein tightly and inhibit the reaction (11)(12). The best in vitro IC 50 of these compounds are Ϸ4 M on Streptococcus faecalis DDl, and their antibacterial activities are not significant (11).…”
mentioning
confidence: 99%
“…The enzymes have similar functions in the biosynthesis of peptidoglycan termini in bacteria, but the capacity of VanA to form D-Ala-D-Lac has a direct correlation with enterococcal resistance to vancomycin. In this paper, we report the crystal structure of VanA complexed with a substrate inhibitor (7) and define the residues involved in substrate binding that are crucial to the resistance mechanism.…”
mentioning
confidence: 99%
“…The monomethyl ester 9 was obtained by partial base-catalyzed hydrolysis of dimethyl ester 8 and was subsequently converted by treatment with thionyl chloride in dichloromethane to chlorophosphonate 10. This strategy revealed the key intermediate chlorophosphonate 10 could be coupled with d-lactic acid methyl ester or d-alanine methyl ester and converted using previously published procedures 8,10,14 to aord the phosphonate 3 and phosphonamidate 1. Similar synthetic Schemes are thoroughly precedented in the literature.…”
mentioning
confidence: 99%
“…The crystal structure of VanX demonstrated that the comparable N±H in substrate d-Ala-d-Ala is hydrogen bonded to the backbone carbonyl of Tyr109. 6 To extend the synthetic route in Scheme 1 to generate additional potential inhibitors of VanX, chlorophosphonate 10 was coupled with methyl mercaptoacetate and deprotected using standard procedures 8,10,14 to yield the phosphothioate 2. This compound was shown to be stable for over a week at 4 C and at pH 7.0.…”
mentioning
confidence: 99%